(untitled) (Al-Academy, 2017)
The following research has been dealing ( Undermining Humanism in Foucault’s thought and its implications in the pop art. meanings and facts which become in the process of the post-modernist.So the research’s problem is to ask for undermining Humanism in Foucault’s thought and how it formed through the formality of processors and the technical and stylistic and contents in pop art.. How are these technical aspects interact with each other to undermine the humanism in Foucault’s mind and with system humanity, intellectual and social relations in the post-modern society . The contents of the first chapter, is the aim of the research, which aims to undermine know humanism in Foucault’s mind and its implications in pop art , within the limits of contemporary fine art in Europe and America during the (1965) to (1999) Then included second chapter on the theoretical framework, the theoretical framework contains three sections: the first of which dealt with undermine humanism at the mind of post- modernism, while the second section included: undermine humanism at the Foucault’s mind and the third section explained the undermine humanism in pop art. The third chapter has dealt with research procedures, hence the spam of the research community, the researcher has obtained only (50) only work of this community the research sample has chosen in deliberate way according to a group of justifications and it determined by (5) models for the research sample and the researcher adopted at the analysis of the sample models on the descriptive approach and with style of content analysis and this chapter has also included build the mean in its initial and final way. While the fourth chapter included the results of the research and its conclusions , in addition to proposals and recommendations . Among the most results findings by the researcher :1.Undermined with disassembly are matching by undermining human , killed him and tortured him and this is a real summary exercised its presence in contemporary life, and this represents a metaphor of what disappears behind the masks, It is the silence , meaninglessness and passivity to the pain and violence of Western society and all this relates to ( Foucault ’s) mind , who wanted to undermine human and marginalized and .( this in turn appeared in pop art and reflected in the models (1, 5)